Difference between revisions of "TADM2E 1.13"

From Algorithm Wiki
Jump to: navigation, search
(Recovering wiki)
(Redirected page to UNTV)
Line 1: Line 1:
Call the statement <math>S_n</math> and the general term <math>a_n</math><br>
+
#REDIRECT [[UNTV]]
 
 
<b>Step 1:</b> Show that the statement holds for the basis case <math>n = 0</math><br>
 
 
 
:<math>a_0 = 0 \cdot (0 + 1)(0 + 2) = 0</math>
 
<br><br>
 
:<math>S_0 = \frac {0 \cdot (0 + 1)(0 + 2)(0 + 3)} {4} = \frac {0} {4} = 0 </math><br>
 
 
 
Since <math>a_n = S_n</math>, the basis case is true.<br><br>
 
 
 
<b>Step 2:</b> Assume that <math>n = k</math> holds.
 
:<math>S_k = \frac {k(k + 1)(k + 2)(k + 3)} {4}</math><br><br>
 
 
 
<b>Step 3:</b> Show that on the assumption that the summation is true for ''k'', it follows that it is true for ''k + 1''.
 
 
 
:<math>
 
\begin{align}
 
S_{k + 1} & = \sum_{i = 1}^k i(i + 1)(i + 2) + a_{k + 1} \\
 
          & = \frac{k(k + 1)(k + 2)(k + 3)} {4} + (k + 1)((k + 1) + 1)((k + 1) + 2) \\
 
          & = \frac{k(k + 1)(k + 2)(k + 3)} {4} + (k + 1)(k + 2)(k + 3) \\
 
          & = \frac{k(k + 1)(k + 2)(k + 3)}{4} + \frac{4 \cdot (k + 1)(k + 2)(k + 3)} {4} \\
 
\end{align}
 
</math><br>
 
 
 
It's easier to factor than expand. Notice the common factor of ''(k + 1)(k + 2)(k + 3)''.
 
:<math>S_{k + 1} = \frac{(k + 1)(k + 2)(k + 3)(k + 4)}{4}</math><br>
 
 
 
This should be equal to the formula
 
<math>S_k = \frac{k(k + 1)(k + 2)(k + 3)}{4}</math>
 
when ''k = k + 1'':<br>
 
:<math>\frac{(k + 1)((k + 1) + 1)((k + 2) + 2)((k + 1) + 3)} {4} =
 
\frac{(k + 1)(k + 2)(k + 3)(k + 4)} {4}</math><br><br>
 
 
 
Since both the basis and the inductive step have been proved, it has now been proved by mathematical induction that S_n holds for all natural n
 
 
 
[[introduction-TADM2E|Back to ''Introduction ...'']]
 

Revision as of 10:13, 31 July 2020

Redirect to: